A Simplified Procedure for Sizing Solar Thermal Systems; Based on National Assessment Methods in the UK and Ireland. - MCCORMACK, SARAH; KINNANE, OLIVER (My University, 2014)
Solar heating systems have the potential to be an efficient renewable energy technology, provided they are sized correctly. Sizing a solar thermal system for domestic applications does not warrant the cost of a simulation. As a result simplified sizing procedures are required. The size of a system depends on a number of variables including the efficiency of the collector itself, the hot water demand and the solar radiation at a given location. Domestic Hot Water (DHW) demand varies with time and is assessed using a multi-parameter detailed model. Secondly, the national energy evaluation methodologies are evaluated from the perspective of solar thermal system sizing. Based on the assessment of the standards, limitations in the evaluation method for solar thermal systems are outlined and an adapted method, specific to the sizing of solar thermal systems, is proposed. The methodology is presented for two common dwelling scenarios. Results from this showed that it is difficult to achieve a high solar fraction given practical sizes of system infrastructure (storage tanks) for standard domestic properties. However, solar thermal systems can significantly offset energy loads due associated DHW consumption, particularly when sized appropriately. The presented methodology is valuable for simple solar system design and also for the quick comparison of salient criteria.
Energy Procedia
Sustainability in Energy and Buildings
Keywords: Domestic hot water; solar thermal systems; aperture area; storage tank; Domestic hot water; solar thermal systems; aperture area; storage tank; Creative Technologies; Smart & Sustainable Planet